Influence of Flanges Geometry on the Shear Behavior of Reinforced Concrete Inverted T-beams - Eman Shallan; ‪mahmoud Abdel-Aziz‬; Nessreen Kassem (Journal of Engineering Research - Egypt, 2023)
Most international codes of practice didn't consider the flange contribution of reinforced concrete T-beams in shear strength. In inverted T-beams loaded on the web, if the flange area is considered in shear strength, the results may be overestimated because after the web cracks open, the aggregate interlock which has a more significant contribution to shear decreases, and shear stresses tend to concentrate at the compression zone, which is located in the web of inverted T-beams. To quantify flange contribution, an experimental program backed by a finite element program based on a nonlinear 3D finite element model was carried out. The experimental program investigates the shear response of beams with varying flange geometry and reinforcement. the results showed that by increasing the flange geometry, the shear strength rises but up to a certain point, the contribution of the flange reinforcement to shear must be neglected. In the current analysis, the greatest contribution of flanges was determined to be 44.5% of total shear resisted by control beam without flange. Furthermore, the numerical model was utilized to visualize and quantify characteristics that are difficult to get experimentally, such as shear stress distribution between the web and the flanges. Also, the model was used to solve a matrix of beams to obtain the maximum shear resistance to make an accurate simplified computational model which shows good agreement with the experimental and finite element results.